Affiliate Business in the Digital Era: A Normative Analysis of Its Legal Status in Islamic Economic Law - Nur Kholisah; Moh Muhibbin; Diyan Isnaeni (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
The rapid development of information and communication technology has created significant changes in the global economy, particularly in digital trade systems known as e-commerce. One of the latest innovations in this field is affiliate marketing, a model that allows third parties to earn commissions through online sales promotions. This study aims to analyze the legal status of affiliate business practices from the perspective of Islamic law. Using a normative juridical or library research method, the study examines primary and secondary legal materials related to contract law and Islamic economic principles. The findings reveal that affiliate business transactions are permissible (mubah) in Islam as long as they comply with the principles of justice, transparency, and the avoidance of prohibited elements such as riba, gharar, and maysir. Conceptually, affiliate marketing corresponds to the contract of wakalah bil ujrah, which involves an agency agreement with compensation for services rendered. Therefore, affiliate marketing can be categorized as a lawful business model in Islamic economic law, provided that its implementation adheres to sharia principles and ethical standards in digital transactions.